Ответ:
[tex] \frac{2}{3} x + 5 = 3 + \frac{7}{9} x \\ \frac{1}{9} x = 2 \\ x = 18[/tex]
[tex] \frac{1}{14} y - 1 = \frac{1}{4} y - \frac{1}{7} y \\ 2y - 28 = 7y - 4y \\ y = - 28[/tex]
[tex]4z - 4 \frac{1}{6} = - 3 \frac{5}{18} - 1 \frac{1}{3} z \\ 5 \frac{1}{3} z = \frac{16}{18} \\ z = - \frac{8 \times 3}{9 \times 16} = - \frac{1}{6} [/tex]
[tex] - 2x + 4 = - \frac{1}{3} x - 21 \\ - 1 \frac{2}{3} x = - 25 \\ x = \frac{25 \times 3}{5} = 15[/tex]
[tex] \frac{2}{3} y + 2 = \frac{1}{2} y - \frac{1}{4} y - 3 \\ \frac{5}{12} y = - 5 \\ y = - \frac{5 \times 12}{5} = - 12[/tex]
Copyright © 2025 SCHOLAR.TIPS - All rights reserved.
Answers & Comments
Verified answer
Ответ:
[tex] \frac{2}{3} x + 5 = 3 + \frac{7}{9} x \\ \frac{1}{9} x = 2 \\ x = 18[/tex]
[tex] \frac{1}{14} y - 1 = \frac{1}{4} y - \frac{1}{7} y \\ 2y - 28 = 7y - 4y \\ y = - 28[/tex]
[tex]4z - 4 \frac{1}{6} = - 3 \frac{5}{18} - 1 \frac{1}{3} z \\ 5 \frac{1}{3} z = \frac{16}{18} \\ z = - \frac{8 \times 3}{9 \times 16} = - \frac{1}{6} [/tex]
[tex] - 2x + 4 = - \frac{1}{3} x - 21 \\ - 1 \frac{2}{3} x = - 25 \\ x = \frac{25 \times 3}{5} = 15[/tex]
[tex] \frac{2}{3} y + 2 = \frac{1}{2} y - \frac{1}{4} y - 3 \\ \frac{5}{12} y = - 5 \\ y = - \frac{5 \times 12}{5} = - 12[/tex]